2018 56th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2018
DOI: 10.1109/allerton.2018.8635980
|View full text |Cite
|
Sign up to set email alerts
|

Single-server Multi-message Private Information Retrieval with Side Information

Abstract: We study the problem of single-server multi-message private information retrieval with side information. One user wants to recover N out of K independent messages which are stored at a single server. The user initially possesses a subset of M messages as side information. The goal of the user is to download the N demand messages while not leaking any information about the indices of these messages to the server. In this paper, we characterize the minimum number of required transmissions. We also present the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…In particular, capacity is known for disjoint colluding sets [4]. The rapidly growing body of literature in this area has produced capacity results for PIR under a rich variety of constraints [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, the capacity for the natural setting of secure storage remains unknown, and relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, capacity is known for disjoint colluding sets [4]. The rapidly growing body of literature in this area has produced capacity results for PIR under a rich variety of constraints [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, the capacity for the natural setting of secure storage remains unknown, and relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…If all databases collude or belong to the same entity, the system essentially becomes a single-database system [13]. The single-database PIR problem has been studied under extended conditions, e.g., side-information [14]- [17]. Here, we investigate singledatabase SPIR under extended conditions, with the goal of making it feasible.…”
Section: Introductionmentioning
confidence: 99%
“…It is straightforward to show that the W -privacy condition (19) implies the following necessary condition on a PIR code.…”
Section: Equivalence Results For Non-linear Schemesmentioning
confidence: 99%
“…It was shown that the side information enables the user to substantially reduce the download cost and still achieve information-theoretic privacy for the requested message. The multi-message extension of PIR-SI, which enables a user to privately download multiple messages from the server, is considered by Heidarzadeh et al [10] as well as Li and Gastpar [11].…”
Section: Introductionmentioning
confidence: 99%